PENERAPAN MODEL PEMBELAJARAN CTL (CONTEXTUAL TEACHING AND LEARNING) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SDNEGERI 010 SEMELINANG DARAT KECAMATAN PERANAP KABUPATEN INDRAGIRI HULU - Ratna, Ratna; Witri, Gustimal; Marhadi, Hendri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrac :Science subjects in primary schools should be given with the aim that students have the ability IPA. For the Science learning outcomes need to be improved by changing the paradigm of learning in elementary education teacher centered to student centered learning. This research is a classroom action research that aims to improve learning outcomes IPA with application of learning models CTL in the fifth grade students of SD Negeri 010 Semelinang Army Peranap Indragiri Hulu subdistrict. The research was conducted on March 12, 2015 to April 9, 2015. The subjects were students of class V Elementary School 010 Semelinang Army totaling 22 people comprising 10 men and 12 women. With the formulation of the problem is the application of learning models CTL (contextual Teahcing and Learning) in the fifth grade students of SD Negeri 010 Semelinang Army Peranap Indragiri Hulu subdistrict. This thesis presents the results of student learning gained through daily test I in the first cycle and the second daily test on the second cycle. In the first cycle an average of 69.10 learning outcomes in the second cycle student learning outcomes on average 76.37, so the average increase of 7.27 students. Mastery learning of individuals in the first cycle, there are 15 people (68.18%), the second cycle, there are 20 people (90.90%). The average activity of teachers in the first cycle was 69.64% with the category enough, on the second cycle was 89.29% with the good category. The average activity of students in the first cycle was 71.43% with the good category, the second cycle was 89.29%. From this study it can be concluded that the application of learning models CTL (contextual Teahcing and Learning) can improve learning outcomes IPA at Elementary School fifth grade students of the District Land 010 Semelinang Peranap school year 2014/2015.Keywords: CTL (contextual Teahcing and Learning) and learning outcomes.